Rapid English Language Courseware for the New Primary School Curriculum: An Evaluation - Tan, Bee Hoon (1994)
When the Ministry of Education of Malaysia launched the Learning- With-Computers Project in 1989, concerned educators felt that there was an acute shortage of local curriculum-related courseware. At this juncture, a pioneer courseware company, produced its first New Primary School Curriculum (NPSC) series, popularly known as RAPID Educational Courseware. The series comprises three major subjects : Bahasa Malaysia, English Language and Mathematics. Because the courseware was new, it was not clear to what extent it confonns to the instructional goals and objectives of the NPSC. It was also not known whether students who used the courseware acquired better skills than those who did not. In view of the urgency to provide such feedback, this evaluation study, which focussed on one major subject i.e. English Language, was conducted. The study aims to suggest guidelines for overall improvement of the design and use of the RAPID English Language Courseware (abbreviated RELC (NPSC)); henceforth indirectly encouraging the production of better courseware. The study employed both formal and informal evaluation. The latter focussed on content and design analysis of the courseware, and the former involved an effectiveness experiment which compared the language improvement of two groups of primary students. One group used the RELC (NPSC) in the computer laboratory, and another followed the tuition class.